PENGARUH KEPEMILIKAN SAHAM MANAJERIAL,DEWAN KOMISARIS INDEPENDEN, DAN GREEN PRODUCTINNOVATION TERHADAP NILAI PERUSAHAAN - Desy Angelina Pandiangan (2023)
This research is a quantitative study that aims to determine the effect of managerial ownership, independent board of commissioners, and green product innovation on firm value as measured by Tobin's q. The samples obtained in this study came from LQ45 stock companies listed on the Indonesia Stock Exchange in the 2018-2022 period which were selected using the purposive sampling method. The data obtained in this study were 59 companies with a total sample of 170 data. The technique used in testing the variables is using a regression model selection test, classical assumption test, multiple linear regression test, and hypothesis testing using STATA software version 16 and a significance level of 5% (0.05). The results obtained from testing that (1) managerial ownership has a positive effect on firm value, (2) independent commissioners do not have a significant effect on firm value, and (3) green product innovation does not have a significant effect on firm value.